Resource Accessibility and Productivity among Women Crop Farmers in Borno State, Nigeria - Ojo, Catherine O; Bila , Yakubu; Iheanacho , Andrew C (Asian Journal of Agriculture and Rural Development, 2012)
The objective of this study was to determine resource accessibility and productivity among crop farming women in Borno State, Nigeria. Likert scale was used to describe women’s accessibility to agricultural production resources. The Maximum Likelihood Estimates (MLE) of the stochastic frontier production function (SFPF) was used to estimate the production and technical inefficiency determinants as a measure of productivity of the respondents. Results indicated that respondents had low access to most of the agricultural productivity resources considered in the study. Furthermore, the gamma of 0.7865 was significant at 1%, revealing that over 78% of the variation in the productivity of respondents was attributable to technical inefficiency factors. This underscores the fact that low access to technical efficiency resources contributes immensely to productivity losses among women farmers It was recommended that access to technical efficiency factors including credit, education, extension contact and membership of cooperatives need to be enhanced among women farmers to empower women to effectively access and utilize resources of agricultural productivity.